Modern Innovations and Traditions in Preschool Education - Mamasakhatovna, Yuldasheva Feruza (European Journal of Life Safety and Stability (2660-9630), 2023)
The article is devoted to the problem of the correlation of traditions and innovations in the activities of preschool educational organizations. Innovative activity, having become an integral part of the process of preschool education, is based on traditional, well-established and significant principles for the system of preschool education, forms and methods of work on the development of the child. The article defines traditions and innovations, classifies innovations in preschool education, and highlights those positions that are really new today: inclusion, variable preschool education programs, and new technologies.